2011
DOI: 10.1021/ic2003782
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis with Structural and Electronic Characterization of Homoleptic Fe(II)- and Fe(III)-Fluorinated Phenolate Complexes

Abstract: Four Fe(III) compounds and one Fe(II) compound containing mononuclear, homoleptic, fluorinated phenolate anions of the form [Fe(OAr)(m)](n-) have been prepared in which Ar(F) = C(6)F(5) and Ar' = 3,5-C(6)(CF(3))(2)H(3): (Ph(4)P)(2)[Fe(OAr(F))(5)], 1, (Me(4)N)(2)[Fe(OAr(F))(5)], 2, {K(18-crown-6)}(2)[Fe(OAr(F))(5)], 3a, {K(18-crown-6)}(2)[Fe(OAr')(5)], 3b, and {K(18-crown-6)}(2)[Fe(OAr(F))(4)], 6. Two dinuclear Fe(III) compounds have also been prepared: {K(18-crown-6)}(2)[(OAr(F))(3)Fe(μ(2)-O)Fe(OAr(F))(3)], 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 54 publications
3
27
0
Order By: Relevance
“…In contrast, a similar linear transit study of the known [M(OC 6 F 5 ) 4 ] 2À ions, shows that these compounds with only monodentate ligands and dihedral angles of 76.98 (Co) [19] and 80.58 (Fe), [18] are much more stable in a tetrahedral geometry than square-planar, although the square-planar [Cu(OC 6 F 5 ) 4 ] 2À is also known. [19] In the absence of the chelate rings, four electronically similar donor groups give quite a distinct result.…”
Section: àmentioning
confidence: 98%
See 4 more Smart Citations
“…In contrast, a similar linear transit study of the known [M(OC 6 F 5 ) 4 ] 2À ions, shows that these compounds with only monodentate ligands and dihedral angles of 76.98 (Co) [19] and 80.58 (Fe), [18] are much more stable in a tetrahedral geometry than square-planar, although the square-planar [Cu(OC 6 F 5 ) 4 ] 2À is also known. [19] In the absence of the chelate rings, four electronically similar donor groups give quite a distinct result.…”
Section: àmentioning
confidence: 98%
“…, M = Fe, [18] in which OAr = OC 6 F 5 or 3,5-OC 6 [22] Ni. [20] Spectroscopic [20] and computational [18] work have shown that these fluorinated ligands are medium field ligands, on par with OH À and F À , and stronger than NCO À .…”
Section: àmentioning
confidence: 99%
See 3 more Smart Citations